Childcare Digital Book for Infants and Children - Azrie, Ahmad Fakhrul Hadi; Mat Rejab, Mazidah (Applied Information Technology And Computer Science, 2024)
The management of infant and child health examinations in traditionally relied on physical record books, leading to challenges like loss and complexity in record management. Addressing this, the project aimed to develop Childcare Digital Book, a mobile application offering a modern alternative. Using Agile development approach, by leveraging Flutter framework and Firebase, the app was developed after extensive research on traditional book limitations and user requirements through interviews, surveys, and market analysis. This app streamlines health records, appointments, and access to child health data, enhancing healthcare efficiency for parents and providers. By modernizing child healthcare, it promises improved access to vital health information besides signifies progress in Malaysia’s healthcare and potentially sets a model for modernization in other sectors.